Patient satisfaction with general practice in urban and rural areas of Scotland - Isha Iqbal; Lucy Thompson; Philip Wilson (James Cook University, 2021)
Introduction: The aim of the study was to determine if there is a systematic difference between urban and rural patient experience across Scottish general practices associated with urban/rural status measured by the Scottish eightfold urban/rural classification (UR8). Methods: The study was a secondary analysis of data from the Scottish National Health and Care Experience (HACE) survey of patient satisfaction. Cross-sectional and longitudinal datasets were used to illustrate recent findings and temporal trends. The general practices were matched to HACE survey responses and practice code numbers, which in turn were assigned to a code from the UR8 classification (where UR8 is the most rural and UR1 is the most urban) based on postal code. Due to the low number of practices in some UR8 classifications, categories (UR3-5 and UR6-8) were merged for some analyses. Patient-centred care and continuity of care were assessed based on a selection of questions from the 2017/18 survey where respondents were asked to indicate their level of agreement to numerous statements. The response alternatives to the survey questions were 'very positive', 'positive', 'neutral' and 'negative'. Responses of 'very positive' and 'positive' were aggregated to give 'percentage satisfied'. One-way analysis of variance (ANOVA) was used to assess cross-sectional and longitudinal datasets. Results: A total of 1008 GP practices participated in the 2009/10 HACE survey. Of these, 166 practices were excluded from the study for a range of reasons including closures or mergers. A total of 71 practices had changed UR8 classification between 2010 and 2018 and were also excluded. Five very small practices were excluded as these were considered likely to offer services to atypical populations. Data relating to 766 practices were analysed: average response rates were 18-31%, highest in the most remote areas. In the most recent 2017/18 survey results, there were significant differences in percentage positive responses by merged UR8 category for all questions (all p<0.001): patients in the most rural/remote UR6-8 practices were significantly more satisfied for all questions analysed. For some questions, such as 'I was listened to', UR1 was significantly different from UR2 and UR3-5, but there was no significant difference between UR2 and UR3-5. For all questions, patients in UR3-5 practices reported having the lowest satisfaction. Overall satisfaction was lowest for the questions 'I was given the opportunity to involve the people that matter to me' and 'I knew the healthcare professional well'. Regarding the longitudinal data for patient satisfaction, patients within the UR6-8 classifications tend to be most satisfied, and this trend has stayed consistent over time. In particular, 'I was given enough time' showed a statistically significant difference across all years for UR6-8, compared to the other urban/rural categories, which did not differ significantly. Conclusion: Individuals residing in remote and rural areas of Scotland tend to have the highest satisfaction with their general practice in terms of patient-centred care and continuity of care. Residents in suburban populations tend to be least satisfied in the same domains. Additional work is needed in order to understand the underlying mechanisms behind these findings.